Comparative Literature: Exploring Folktales “Ular N’daung Dan Si Bungsu” And “The Legend of White Snake” - Dyah Ratna Mufidah; Arju Susanto; Kurnia Rachmawati (Institut Agama Islam Negeri Palopo, 2024)
Folktales are one of the widespread literary works in the community. Folktales in one region may differ in themes, storylines, and aspects from the other. Examples of such differences can be seen in the Indonesian folktale